Analysis of Grade VI Students' Mathematical Creative Thinking Skills in Solving Problems on the Topic of Circles - Oktorina Ponco Rahayu; Ristiana Dyah Purwandari (UM Purwokerto Press, 2025)
This research aims to describe how the mathematical creative thinking abilities of grade sixth students in solving mathematical problems on circle material at SD Negeri 1 Mantrianom with the indicators of mathematical creative thinking ability used being fluency, flexibility, originality and elaboration. This research was conducted on 23 class VI students using a qualitative descriptive method. The instrument used was 4 descriptive questions which covered students' mathematical creative thinking abilities on circle material. The results of the research show that students' mathematical creative thinking abilities have a percentage of 62.5% which is included in the category of creative.